2014
DOI: 10.1080/09644016.2014.921462
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in environmental concern among Swedish citizens and politicians

Abstract: Numerous studies find modest, consistent gender differences in environmental concern within the general publics of North American and European countries, but results from the few studies of gender differences among politicians are inconsistent. We test if women report stronger environmental concern than men across four levels of the Swedish polity, utilising three data sets: a representative sample of the general public, a survey of all representatives in municipal-level and county-level councils, and a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
5
32
1
1
Order By: Relevance
“…Indeed, it is possible that females who pursue leadership roles in a predominantly male environment are similar to males (Adams and Funk, 2012). Consistent with this proposition, Sundstrom and McCright (2014) do not find robust evidence for gender differences in environmental concerns among Swedish parliamentarians although such gender differences are observed in the general public in Sweden. In the context of the US, however, Fredriksson and Wang (2011) find that female parliamentarians in the House of Representatives have more pro-environmental views compared to their male counterparts.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, it is possible that females who pursue leadership roles in a predominantly male environment are similar to males (Adams and Funk, 2012). Consistent with this proposition, Sundstrom and McCright (2014) do not find robust evidence for gender differences in environmental concerns among Swedish parliamentarians although such gender differences are observed in the general public in Sweden. In the context of the US, however, Fredriksson and Wang (2011) find that female parliamentarians in the House of Representatives have more pro-environmental views compared to their male counterparts.…”
Section: Introductionmentioning
confidence: 80%
“…Overall, women are more likely to suffer employment and earnings loss (Willinger 2008), are at an increased risk of violence following a disaster (Enarson 1999), and are burdened with a disproportionate share of care-work (Fothergill 1999). The literature is also replete with evidence that these disproportionately felt effects translate into higher overall environmental concern than men (Sundström and McCright 2014;McCright and Xiao 2014;Yates et al 2015). Within households, research finds that women's risk mitigation and disaster recovery needs are often sacrificed as decision-making power is maintained by male partners who discourage action (Enarson and Scanlon 1999;Milfont and Sibley 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women's attitudes can be expected to influence policymaking. A quantitative study by Sundström and McCright [54] focused on the link between gender and environmental attitudes in Sweden. It looked at four levels of the polity and demonstrated a significant gender gap regarding the degree of environmental concern among the citizens, among the municipal councils and at the regional level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It looked at four levels of the polity and demonstrated a significant gender gap regarding the degree of environmental concern among the citizens, among the municipal councils and at the regional level. Only in the national parliament was the difference not statistically significant [54]. Various surveys have shown that women in the EU and the US are more concerned about climate issues than men [55][56][57][58][59].…”
Section: Literature Reviewmentioning
confidence: 99%